2023
DOI: 10.3389/fendo.2023.1158013
|View full text |Cite
|
Sign up to set email alerts
|

Association between different metabolic phenotypes of obesity and thyroid disorders among Chinese adults: a nationwide cross-sectional study

Abstract: BackgroundIncreased body mass index (BMI) and metabolic abnormalities both have potential associations with thyroid disease. The aim of this study was to investigate the correlation between different metabolic phenotypes of obesity and thyroid disorders using nationwide data from China.MethodsData were collected from a cross-sectional survey called the Thyroid Disorders, Iodine Status, and Diabetes Epidemiological Survey conducted between 2015 and 2017 in China. A total of 69007 subjects aged 18 years or older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Another Chinese scholar, Shan, Zhongyan, also conducted a large cohort study to investigate the association between obesity and different metabolic phenotypes of thyroid disease in Chinese adults. [20] The results were analyzed by the corresponding authors. Among the results of the analysis of co-cited authors, REINEHR T has the most citations with 119.…”
Section: Discussionmentioning
confidence: 99%
“…Another Chinese scholar, Shan, Zhongyan, also conducted a large cohort study to investigate the association between obesity and different metabolic phenotypes of thyroid disease in Chinese adults. [20] The results were analyzed by the corresponding authors. Among the results of the analysis of co-cited authors, REINEHR T has the most citations with 119.…”
Section: Discussionmentioning
confidence: 99%
“…Teng et al. (year) explored the association between thyroid function and metabolic syndrome and observed that the subclinical hypothyroidism group had higher levels of BMI, waist circumference, SBP, and TG compared to the normal thyroid function group ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using national data from China, a cross-sectional survey named the “Thyroid disorders, Iodine Status, and Diabetes Epidemiological Survey” was carried out between 2015 and 2017 to examine the relationship between several metabolic phenotypes of obesity and thyroid disease. Multivariate logistic regression analysis showed that metabolically unhealthy individuals with and without obesity had an increased risk of SHypo compared to metabolically healthy individuals without obesity [ 28 ]. The results on 5009 consecutive de novo patients admitted for workup and rehabilitation of obesity showed that females and non-smokers had higher TSH levels.…”
Section: Association Between Obesity and Shypomentioning
confidence: 99%
“…In obese patients, leptin levels are correlated with serum TSH levels, and decreased levels of FT4 may be linked to elevated serum TSH levels [ 24 ] ( Figure 1 ). Numerous investigations have demonstrated a negative correlation between FT4 and BMI and a positive relationship between TSH and BMI [ 25 , 26 , 27 , 28 , 31 , 32 , 33 , 34 ]. The old literature suggests that the increase in serum TSH and T3 levels observed in obese individuals could be a physiological mechanism to increase energy expenditure to improve weight gain.…”
Section: Association Between Obesity and Shypomentioning
confidence: 99%